THE KNOWLEDGE MANAGEMENT IN HADITH CODIFICATION - Erika, Erika; Mujiburrahman, Mujiburrahman (RIWAYAH, 2022)
Hadith codification has been carried out since the Prophet Muhammad era and was systematically documented in the 3rd century Hijri. During this period, the hadith codification went through a complicated process. The clerics who wrote hadith books had a standard in collecting, processing, and disseminating hadith. It has similarities with current knowledge management process theory, i.e., create, capture, classify, store, share, and apply. This study examines the knowledge management of hadith codification using the SECI model by Nonaka & Takeuchi. SECI contains four stages, there are Socialization, Externalization, Combination, and Internalization. The authors classify the process of hadith codification into the SECI model. In socialization, it will describe the process of hadith transfer from the Prophet Muhammad to his companions. The externalization stage explains the efforts of the companions to make the hadith into an explicit form. Afterward, the hadith codification process in the 3rd century Hijri is described at the combination stage. The last is internalization which explains the implementation and recreation of hadith into a new form of documentation. The method used is descriptive. Data were collected using historical-comparative research methods from the documents as the main sources and interviews as additional sources. The results of this study are rigorous methods used in the hadith codification in the context of knowledge management. Other findings are the values of the hadith codification process that can be applied in an organization.[Manajemen Pengetahuan dalam Kodifikasi Hadis. Kodifikasi hadis telah dilakukan sejak zaman Nabi Muhammad dan didokumentasikan secara sistematis pada abad ke-3 Hijriah. Selama periode ini, kodifikasi hadis melalui proses yang rumit. Para ulama yang menulis kitab hadis memiliki standar dalam mengumpulkan, mengolah, dan menyebarluaskan hadis. Ini memiliki kesamaan dengan teori proses manajemen pengetahuan saat ini, yaitu membuat, menangkap, mengklasifikasikan, menyimpan, berbagi, dan menerapkan. Penelitian ini mengkaji tentang manajemen pengetahuan kodifikasi hadits menggunakan model SECI oleh Nonaka & Takeuchi. SECI terdiri dari empat tahap, yaitu Sosialisasi, Eksternalisasi, Kombinasi, dan Internalisasi. Penulis mengklasifikasikan proses kodifikasi hadits ke dalam model SECI. Dalam sosialisasi ini akan dijelaskan proses transfer hadits dari Nabi Muhammad SAW kepada para sahabatnya. Tahap eksternalisasi menjelaskan upaya para sahabat untuk menjadikan hadits dalam bentuk eksplisit. Selanjutnya, proses kodifikasi hadits pada abad ke-3 Hijriah digambarkan pada tahap kombinasi. Terakhir adalah internalisasi yang menjelaskan implementasi dan rekreasi hadis ke dalam bentuk dokumentasi baru. Metode yang digunakan adalah deskriptif. Pengumpulan data dilakukan dengan metode penelitian sejarah-komparatif dari dokumen sebagai sumber utama dan wawancara sebagai sumber tambahan. Hasil penelitian ini adalah metode ketat yang digunakan dalam kodifikasi hadits dalam konteks manajemen pengetahuan. Temuan lainnya adalah nilai-nilai proses kodifikasi hadis yang dapat diterapkan dalam sebuah organisasi.]